(untitled) (Scientific journal of the Fergana State University, 2024)
This article delves into the critical realm of youth soccer development, emphasizing the keyl role of coordination skills in shaping individual and team performance. Acknowledging football’s unique demands, the study recognizes the formative years as a key phase marked by rapid physiological and psychological changes, necessitating targeted interventions. Drawing insights from [R. Nurimov]’s research, the literature review underscores the correlation between enhanced coordination and improved player outcomes. [Sh. Allamuratov]’s work informs the complex interplay between physiological and psychological factors, guiding tailored training interventions. Cognitive growth, as revealed by [R. Nurimov], is explored in connection with motor skill acquisition. The proposed methodology advocates integrated learning methods and age-appropriate activities, offering a comprehensive framework for youth soccer development.